1995
DOI: 10.1029/94jb02647
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging of the enigmatic Sudbury Structure

Abstract: The Sudbury Structure on the southern margin of the Superior craton was created by a catastrophic explosion in 1.85 Ga and hosts one of the world's largest Ni‐Cu reserves. As a unique terrestrial geological feature, its genesis has been vigorously debated for more than a century. In an effort to optimize the image from seismic reflection data acquired across the center of the Sudbury Structure, we have developed a straight‐line common midpoint binning strategy and employed cross‐dip corrections. These pseudo‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…Lithoprobe was instrumental in establishing acquisition, processing, and interpretation approaches suitable for the hard-rock environment that is typical to several volcanogenic massive sulfide mining camps across Canada. This includes the Bathurst , Buchans (Spencer et al, 1993;Wright et al, 1994), Manitouwadge (Roberts et al, 2003), Matagami (Milkereit et al, 1992a;Adam et al, 1996Adam et al, , 1998Adam et al, , 2003Calvert and Li, 1999), Noranda (Adam et al, 1992;Verpaelst et al, 1995;Perron and Calvert, 1998), Selbaie (Milkereit et al, 1992b;Perron et al, 1997), Sudbury (White et al, 1994;Wu et al, 1995;Adam et al, 2000;Milkereit et al, 2000), and Thompson (White et al, , 2000 mining camps. During Lithoprobe, seismic reflection methods were proposed as a deep exploration tool that could improve the knowledge of structures and stratigraphy in existing mining camps, but also to provide drilling targets at depths beyond those achieved with conventional geophysical mining methods.…”
Section: Canadamentioning
confidence: 99%
“…Lithoprobe was instrumental in establishing acquisition, processing, and interpretation approaches suitable for the hard-rock environment that is typical to several volcanogenic massive sulfide mining camps across Canada. This includes the Bathurst , Buchans (Spencer et al, 1993;Wright et al, 1994), Manitouwadge (Roberts et al, 2003), Matagami (Milkereit et al, 1992a;Adam et al, 1996Adam et al, , 1998Adam et al, , 2003Calvert and Li, 1999), Noranda (Adam et al, 1992;Verpaelst et al, 1995;Perron and Calvert, 1998), Selbaie (Milkereit et al, 1992b;Perron et al, 1997), Sudbury (White et al, 1994;Wu et al, 1995;Adam et al, 2000;Milkereit et al, 2000), and Thompson (White et al, , 2000 mining camps. During Lithoprobe, seismic reflection methods were proposed as a deep exploration tool that could improve the knowledge of structures and stratigraphy in existing mining camps, but also to provide drilling targets at depths beyond those achieved with conventional geophysical mining methods.…”
Section: Canadamentioning
confidence: 99%
“…CDP sorting was carried out over a straight line because it led to stronger and more continuous reflections than a slalom line (e.g., Wu et al, 1995;Rodriguez-Tablante et al, 2007). Different means of binning were tried to optimize the stack, as will be discussed in more detail in the next section.…”
Section: Standard Processingmentioning
confidence: 99%
“…It is present when the survey line is not perpendicular to the strike of the reflectors (Larner et al, 1979;Wu et al, 1995;Nedimović and West, 2003; O'Dowd et al, Table 2. Processing steps of the seismic reflection survey (see Figure 2).…”
Section: Cross-dip Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The structures as delineated by seismic means depend on many variables such as the volume and extent of melt sheets, the amount of brecciation or damage, and the size of the structure. The number of seismological studies of impact structures has grown substantially over the last few years with studies at scales ranging from hundreds of kilometers over large impact structures such as Chicxulub in Mexico (Morgan et al 2000) and Sudbury (Wu et al 1995;Boerner et al 2000) to smaller structures such as the Mjølnir structure, which is 40 km in diameter (Dypvik et al 2004) in the Barents Sea, and the buried (but not yet confirmed to be an impact) Silverpit structure, which is ~10 km in diameter, that was well resolved in 3-D seismic images (Stewart and Allen 2005). The age range for these seismically studied structures extends from the 2.02 Gyr old Vredefort-Witwatersrand structure of South Africa (cf.…”
Section: Seismological Investigations Of Impact Structuresmentioning
confidence: 99%